Puncture Reduction in Percutaneous Transforaminal Endoscopic Discectomy with HE's Lumbar LOcation (HELLO) System: A Cadaver Study. - Guoxin Fan; Xiaofei Guan; Qi Sun; Annan Hu; Yanjie Zhu; Guangfei Gu; Hailong Zhang; Shisheng He (PLoS ONE)
Background Percutaneous transforaminal endoscopic discectomy (PTED) usually requires numerous punctures under X-ray fluoroscopy. Repeated puncture will lead to more radiation exposure and reduce the beginners' confidence. Objective This cadaver study aimed to investigate the efficacy of HE's Lumbar Location (HELLO) system in puncture reduction of PTED. Study design Cadaver study. Setting Comparative groups. Methods HELLO system consists of self-made surface locator and puncture locator. One senior surgeon conducted the puncture procedure of PTED on the left side of 20 cadavers at L4/L5 and L5/S1 level with the assistance of HELLO system (Group A). Additionally, the senior surgeon conducted the puncture procedure of PTED on the right side of the cadavers at L4/L5 and L5/S1 level with traditional methods (Group B). On the other hand, an inexperienced surgeon conducted the puncture procedure of PTED on the left side of the cadavers at L4/L5 and L5/S1 level with the assistance of our HELLO system (Group C). Results At L4/L5 level, there was significant difference in puncture times between Group A and Group B (P<0.001), but no significant difference was observed between Group A and Group C (P = 0.811). Similarly at L5/S1 level, there was significant difference in puncture times between Group A and Group B (P<0.001), but no significant difference was observed between Group A and Group C (P = 0.981). At L4/L5 level, there was significant difference in fluoroscopy time between Group A and Group B (P<0.001), but no significant difference was observed between Group A and Group C (P = 0.290). Similarly at L5/S1 level, there was significant difference in fluoroscopy time between Group A and Group B (P<0.001), but no significant difference was observed between Group A and Group C (P = 0.523). As for radiation exposure, HELLO system reduced 39%-45% radiation dosage when comparing Group A and Group B, but there was no significant difference in radiation exposure between Group A and Group C whatever at L4/L5 level or L5/S1 level (P>0.05). There was no difference in location time between Group A and Group B or Group A and Group C either at L4/L5 level or L5/S1 level (P>0.05). Limitations Small-sample preclinical study. Conclusion HELLO system was effective in reducing puncture times, fluoroscopy time and radiation exposure, as well as the difficulty of learning PTED. (2015-RES-127).